Bridging organizations in agricultural carbon markets and poverty alleviation: An analysis of pro-Poor carbon market projects in East Africa. (July 2016) - Lee, Jean; Ingalls, Micah; Erickson, Jon D.; Wollenberg, Eva
Highlights: Agricultural carbon markets have mismatches arising from interscalar dynamics. Bridging organizations serve as a link for farmers to access the carbon market. Donors and project developers shape how bridging organizations mediate mismatches. Trade-offs limit the degree to which the "triple-win" can be achieved. International carbon markets cannot inherently address development needs. Abstract: International agricultural carbon market projects face significant challenges in delivering greenhouse gas mitigation objectives whilst also seeking to provide additional benefits for poverty alleviation. The carbon credit producer (the smallholder farmer) and carbon credit buyer in the carbon market transaction typically operate at different spatial and temporal scales. Buyers operate at a global scale, responding to opportunities for financial speculation and both private and public climate action plans. Farmers operate within households, farms, and immediate agricultural landscapes, pursuing livelihood and food security needs. These different scales often result in mismatches of timing, payment, and knowledge in market transactions and can be partially rectified by project developers who serve to broker the relationship between the farmers and the buyers. We examined eight East African agricultural carbon market projects to determine how project developers function as bridging organizations and minimize the mismatches between these actors. Results show that projects better bridged the timing and payment gap between buyers and producers when project developers provided non-monetary benefits or direct monetary assistance to farmers. However, knowledge gaps remained a significant barrier for farmers wishing to participate in the market. We discuss how project developers brokered relationships in ways that reflected their interests and highlight the limitations, trade-offs, and challenges that must be overcome if win-win outcomes of poverty alleviation and climate change mitigation are to be realized.